2013
DOI: 10.1038/ejhg.2013.138
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous 237-kb deletion at 1p31 identified as the locus for midline cleft of the upper and lower lip in a consanguineous family

Abstract: Orofacial clefts are congenital defects that vary widely in type and severity, and can occur in isolation or in association with a variety of other defects. Herein, we describe a consanguineous family afflicted with a unique form of orofacial clefting manifesting as a facial midline defect that also involves mandibular and maxillary structures. All four affected sibs had median clefts of the upper and lower lips, tooth misalignment, and poor oral hygiene. Linkage analysis of 17 family members identified a 15.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Several studies have documented their findings regarding 1p chromosomal region. A novel homozygous intergenic deletion of 237-kb at 1p31 was reported in four affected siblings of consanguineous marriage and 1p31 is an autosomal recessive locus [ 14 ]. It was previously reported that locus 1p34 has a positive linkage among families with a history of Van der Woude syndrome (VWS) that brought it to the interest because it closely resembles the phenotype of NSCLP [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have documented their findings regarding 1p chromosomal region. A novel homozygous intergenic deletion of 237-kb at 1p31 was reported in four affected siblings of consanguineous marriage and 1p31 is an autosomal recessive locus [ 14 ]. It was previously reported that locus 1p34 has a positive linkage among families with a history of Van der Woude syndrome (VWS) that brought it to the interest because it closely resembles the phenotype of NSCLP [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Linkage studies have revealed several candidate regions studied in different populations. A consanguineous family with 17 members has reported to have homozygous 237-kb deletion at locus 1p31 among the family members that cause cleft lip [ 14 ]. Three regions of chromosome 1; 1p36, 1q21 and 1q32-42.3, which 1p36 regions had positive scores by parametric linkage approach and pairwise analysis found susceptibility gene on 1q21 and 1q32-42.3 regions in 38 families of NSCLP from Northeastern Italy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric diagnoses included attention deficit a Adapted from references. [1][2][3][4][5][6][7][8][9] Note: AE, may or may not have this clinical feature. hyperactivity disorder (ADHD), sensory integration dysfunction, and speech articulation difficulty.…”
Section: Siblingmentioning
confidence: 99%
“…Interstitial deletions of chromosome 1p31 have been reported in at least 10 individuals and phenotypic characteristics summarized by Mircher et al 1 Clinical findings included intellectual disability, hypertonia, failure to thrive, microcephaly, broad nasal tip, tendency for an open mouth, micrognathia, short neck, fifth finger clinodactyly, and tapering fingers. Additional features described more recently included short stature, obesity, facial asymmetry, hypodontia, 2 ventriculomegaly, hypogenesis of the corpus callosum, abnormal external genitalia, 3 prominent supraorbital ridges, pectus excavatum, high-arched palate, 4 strabismus, midline cleft of the upper and lower lip, and autism spectrum disorder 5,6 (►Table 1). Neuropsychiatric or behavioral phenotypes for chromosome 1p31 deletion have been poorly characterized to date beyond autism spectrum disorder and intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…Linkage studies have successfully revealed several different candidate loci studied in different populations. For example, a consanguineous family with 17 members was reported to have a homozygous 237‐kb deletion at locus 1p31 among the family members that cause cleft lip (Yıldırım, Kerem, Köroğlu, & Tolun, ). There are a lot of studies that revealed the causative genes to nonsyndromic cleft lip palate (NSCLP) formation such as TGF family, FGF family, cleft lip, and palate have been associated transmembrane protein 1 ( CLPTM1 ), special AT‐rich sequence‐binding protein 2 ( SATB2 ), and small ubiquitin‐like modifier 1 ( SUMO1 ) and IRF6 (Carter et al, ; Nie, Luukko, & Kettunen, ; Pauws & Stanier, ; Scapoli et al, ).…”
Section: Introductionmentioning
confidence: 99%